Genetic Relatedness among Duku, Kokosan, and Pisitan in Indonesia Based on Random Amplified Polymorphic DNA Markers - Laila Hanum; Rina Sri Kasiamdari; S. Santosa; R. Rugayah (Indonesian Journal of Biotechnology, 2012)
Genetic relatedness among duku, kokosan, and pisitan from Indonesia were investigated using random amplified polymorphic DNA (RAPD) markers. Eleven primers (OPA-01, OPA-02, OPA-10, OPB-07, OPB-11, OPB-12, OPB-15, OPT-16, OPU-14, OPU-19, and OPU-20) were used for amplification and yielded a total of 174 DNA bands, of which 167 were polymorphic. Primer OPA-10, OPB-11, OPB-12, OPB-15, and OPU-19 produced all of the polymorphic DNA bands. The size of the amplified DNA fragments ranged from 41-1546 bp. The dendrogram separated into two clusters at a genetic similarity coefficient of 0.76. The cluster 1 consisted of subclusters duku and several pisitan (pisitan OKI, pisitan Sleman, pisitan Hatu, pisitan Punggur, and pisitan Tanjung), and cluster 2 consisted of subclusters kokosan and pisitan. In the kokosan subclusters, including duku Drendan. Dendrogram supported the determination of taxonomic status of duku, kokosan, and pisitan as one species, namely Lansium domesticum Corr. and its divided into two groups, namely L. domesticum ’duku group’ and L. domesticum ’pisitan-kokosan group’. Thus, RAPD analysis was useful tool for determining the genetic variation and the genetics relatedness among duku, kokosan, and pisitan in Indonesia.Key words: duku, kokosan, pisitan/langsat, genetic relatedness, RAPD